KRAS and BRAF mutation status in circulating colorectal tumor cells and their correlation with primary and metastatic tumor tissue. Issue 1 (9th February 2013) - Mostert, Bianca; Jiang, Yuqiu; Sieuwerts, Anieta M.; Wang, Haiying; Bolt‐de Vries, Joan; Biermann, Katharina; Kraan, Jaco; Lalmahomed, Zarina; van, Anne; de, Vanja; van der, Petra; Ramírez‐Moreno, Raquel; et al.
<x xml:space="preserve">Abstract</x> Although anti‐EGFR therapy has established efficacy in metastatic colorectal cancer, only 10‐20% of unselected patients respond. This is partly due to KRAS and BRAF mutations, which are currently assessed in the primary tumor. To improve patient selection, assessing mutation status in circulating tumor cells (CTCs), which possibly better represent metastases than the primary tumor, could be advantageous. We investigated the feasibility of KRAS and BRAF mutation detection in colorectal CTCs by comparing three sensitive methods and compared mutation status in matching primary tumor, liver metastasis and CTCs. CTCs were isolated from blood drawn from 49 patients before liver resection using CellSearch™. DNA and RNA was isolated from primary tumors, metastases and CTCs. Mutations were assessed by co‐amplification at lower denaturation temperature‐PCR (Transgenomic™), real‐time PCR (EntroGen™) and nested Allele‐Specific Blocker (ASB‐)PCR and confirmed by Sanger sequencing. In 43 of the 49 patients, tissue RNA and DNA was of sufficient quantity and quality. In these 43 patients, discordance between primary and metastatic tumor was 23% for KRAS and 7% for BRAF mutations. RNA and DNA from CTCs was available from 42 of the 43 patients, in which ASB‐PCR was able to detect the most mutations. Inconclusive results in patients with low CTC counts limited the interpretation of discrepancies between tissue and CTCs. Determination of KRAS and BRAF mutations in CTCs is challenging but feasible. Of the tested methods, nested ASB‐PCR, enabling detection of KRAS and BRAF mutations in patients with as little as two CTCs, seems to be superior.